O crânio de Eira barbara (Carnivora: Mustelidae) do Brasil: variações ontogenéticas, sexuais e geográficas - Loss, Mateus Cruz (2020)
The cranial morphology of carnivores presents a high variation among their species in response to different factors, such as geographic gradients, genetic differences expressed by the phenotype throughout development, niche divergences,